Architectures et nations. Le cas du Schleswig au regard d’autres régions frontalières en Europe - Peter Dragsbo (In Situ, 2019)
Looking back at the five analyzed border regions, one might conclude that the relations between nation and nationality on one hand and architecture on the other hand demonstrate interesting similarities and differences. Thus, Schleswig and Lorraine had much in common regarding to national schism and the development of a counter-architectural style in opposition to the vociferous German architectural politics. Contrary to Schleswig, the French-minded architects chose a nostalgic ´old Paris´ style, whereas the Danish movement in North Schleswig kept in close connection to contemporary Danish architecture. However, neither of the two parts in Lorraine developed a distinct vernacular style. Thus, Schleswig and Alsace underwent a more parallel development of a vernacular style, accepted by all, although the Schleswig Heimatstil was still considered either as a German-Schleswig style or a Danish-Schleswig style by the two national parts, whereas the Alsatian vernacular style rather symbolized a widespread wish for autonomy. Looking at Posen and Western Prussia as well as South Tyrol, none of the irredenta movements cared much about architecture, seeking the national battlefields in other arenas, in particular language, land-ownership and public presence. The German politics of architecture, especially the national romanticism of Emperor Wilhelm II and Franz Schwechten, can be seen as an attempt to solve the problem with the historical and cultural dissimilarity of the Reich. Nevertheless, the demonstrations of the imperial style were particularly directed towards the selected German ´border fortresses´ of Metz and Poznan. Niels Wilcken has interpreted this mechanism as expression of a doubtfully legitimate claim for power in a border region with a disputed state of affairs´. In spite of all borders and national divides one should not forget, however, the strong transversal impact from the great currents of European architecture as well as the influence from the architectural academies. Thus, a South German regionalism extended its influence from the Munich academy not only to Bavaria, but to Austria, Tyrol and Alsace, too. Another example is the Strasbourg neo-classicism from the years before and after World War I, which was originally developed at the academies of Stuttgart and Karlsruhe and kept its status as the dominating style on both sides of the Rhine until World War II. Likewise the Schleswig Heimatstil – amalgamated with the Danish Bedre Byggeskik style – was usable for all national parts until the post-World War II years. Speaking lastly of border region architecture as heritage, one must underline that every nation has a responsibility for the heritage inside its borders, no matter which side created the actual buildings and monuments. In matter of fact, the maintenance of the heritage from the ´other parts´ should not only be a accepted, but also a consciousness of the importance of the ´foreign´ heritage that could highlight one´s own history and culture is paramount, enabling a more genuine understanding of both sides. Therefore researchers, heritage authorities and historians have a common responsibility for turning national heritages into common heritage.